The Development of the Breastfeeding Model of the Postpartum Mothers in Selaphum Hospital Roi-Et Province - Polkhacha, Witchanee (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The purpose of this research was to study the effect of the development of breastfeeding patterns of postpartum mothers. Selaphum Hospital Roi Et Province The sample group was a group of participants who were pregnant women. Gestational age from 34 weeks - until after the birth of infants aged 6 months: 60 were divided into control groups and experimental groups of 30 persons each. The research instruments were the Breastfeeding Promotion Program. and the breastfeeding knowledge assessment form Statistics used in data analysis with percentage values standard deviation and the test and the tee value. The results showed that: 1. The effect of using the breastfeeding promotion model of postpartum mothers. Compare the mean of the mothers' breastfeeding knowledge of the experimental group and the control group. before and after participating in the activity Between the experimental group and the control group before participating in the model development, there was no statistically significant difference (p>.05). After participating in the activity, the experimental group had mean breastfeeding knowledge. of the mother after giving birth statistically significantly higher than the control group (p<.01). and 2. The effect of the development of the breastfeeding promotion model After receiving knowledge of mother's breastfeeding after giving birth The experimental group had higher mean scores on breastfeeding knowledge than before receiving the knowledge. and was significantly higher than the control group (p<.05). The mean of prenatal breastfeeding knowledge between the control group and the experimental group was not statistically different ( p>.05).